ANALISIS FATWA MAJELIS ULAMA INDONESIA DAN NAHDLATUL ULAMA TENTANG PERKAWINAN BEDA AGAMA - Santoso, Rudi (Nurani, 2019)
Interfaith marriages are marriages between people of different faiths, such as marriages of Muslims and non-Muslims, both polytheists and pagan scholars. As a universal religion, Islam views that humans are one unity of the Ummah Wahidah community between individuals and individuals, and between one ethnic group and another ethnic group, there is no difference in the degree of humanity, the difference is the level of piety Allah. For this reason, in terms of marriage, Islam does not question differences in heredity, nationality and or citizenship, but religious differences are the focus of the problem, so that cases of interfaith marriages appear. This research aims to find out the fatwas of two major institutions in Indonesia namely the Indonesian Ulema Council and Nahdlatul Ulama. This study examines the fatwa and legal basis of the fatwa of the Indonesian Ulema Council and Nahdlatul Ulama on interfaith marriages then analyzes the two fatwas and correlates with the context of Indonesianism and the development of the times. The results showed that the Indonesian Ulema Council as an ulama organization in the country forbade interfaith marriages. This fatwa was issued by basing on the arguments of the Koran, hadith, and using the principles of fiqhiyyah and ushuliyah. The prohibition of interfaith marriages is a form of prudence, given the many mudharat arising from such marriages. Nahdlatul Ulama also stressed the marriage between Muslims and non-Muslims is forbiden and illegitimate. The decision of the Lajnah Bahtsul Masail is based on the understanding of the book of Tuhfah al-Tullab bi Sharh al-Tahrir and Hashiyah al-Sharqawi. Muslim women can only be married to Muslim men because all scholars agree to forbid Muslim women from marrying non-Muslim men. Likewise Muslim men can only marry Muslim women. For a number of reasons, it is unlikely to attract women who are Jewish or Christian to convert to Islam. There are many other ways to get people into Islam. Keywords: Fatwa, MUI, Nahdlatul Ulama, Perkawinan Beda Agama